Multiuser communication using adaptive time reversal with moving transmitter. (11th June 2018) - Shimura, Takuya; Kida, Yukihiro; Deguchi, Mitsuyasu; Watanabe, Yoshitaka
Abstract: The effect of transmitter movement in multiuser underwater acoustic communication using adaptive time reversal is studied in this paper. In an underwater acoustic channel, Doppler frequency shifts are very large owing to the low acoustic propagation speed, and they have different values depending on the propagation angle of each multipath. These problems are critical to orthogonal frequency division multiplexing (OFDM), which is widely used as the representative method. On the other hand, by time reversal, different frequency shifts are converged to one frequency shift by wave focusing. This advantageous characteristic was confirmed by normal mode simulation. At-sea experiments for multiuser communication with two transmitters taking into consideration transmitter movement were also carried out. As a result, it was found that adaptive time reversal enables multiuser communication independently of the velocity of the moving transmitter even under multiuser interference.